Parasitic resistive switching uncovered from complementary resistive switching in single active-layer oxide memory device. (21st November 2017) - Zhu, Lisha; Hu, Wei; Gao, Chao; Guo, Yongcai
Abstract: This paper reports the reversible transition processes between the bipolar and complementary resistive switching (CRS) characteristics on the binary metal-oxide resistive memory devices of Pt/HfO x /TiN and Pt/TaO x /TiN by applying the appropriate bias voltages. More interestingly, by controlling the amplitude of the negative bias, the parasitic resistive switching effect exhibiting repeatable switching behavior is uncovered from the CRS behavior. The electrical observation of the parasitic resistive switching effect can be explained by the controlled size of the conductive filament. This work confirms the transformation and interrelationship among the bipolar, parasitic, and CRS effects, and thus provides new insight into the understanding of the physical mechanism of the binary metal-oxide resistive switching memory devices.